Significantly Improved Dielectric Performance of All‐Organic Parylene/Polyimide/Parylene Composite Films with Sandwich Structure. Issue 2 (27th September 2022) - Ahmad, Aftab; Liu, Guanghui; Cao, Shimo; Liu, Xuepeng; Luo, Jinpeng; Han, Li; Tong, Hui; Xu, Ju
Abstract: The development of novel polymer dielectrics with enhanced dielectric performance is a great challenge for application of film capacitors in modern electronics and electrical systems. Herein, an innovative approach of chemical vapor deposition polymerization technology is proposed to prepare the all‐organic sandwich structured parylene/polyimide/parylene (Py/PI/Py) composite films by employing poly(chloro‐para‐xylylene) (parylene C) as the outer layers and polyimide (PI) as the inner layer. The Py/PI/Py composites exhibit superior thermal resistance and outstanding mechanical properties. Moreover, thanks to the interfacial effect which contributes to reinforcing the dielectric response and the thickness effect which facilitates improving the breakdown strength, the dielectric performance of Py/PI/Py composites has been enhanced significantly. Accordingly, dielectric constant of 4.52–5.09, dissipation factor of 0.21–1.01%, and breakdown strength of 307–460 MV m −1 are achieved. Besides, notable energy storage performance is also obtained in Py/PI/Py composite dielectrics. Consequently, this novel application of chemical vapor deposition polymerization method in preparing all‐organic multilayered polymer composite films with sandwich structure shows promising potential in film capacitor applications in harsh conditions. Abstract : The chemical vapor deposition polymerization technology is innovatively proposed to prepare all‐organic sandwich structured parylene/polyimide/parylene composite films. The composite dielectrics maintain excellent thermal resistance and superior mechanical properties. Moreover, the enhanced dielectric constant and breakdown strength, as well as notable energy storage performance are obtained in the parylene/polyimide/parylene composites, which would be promising candidates for film capacitors.